Recent developments of hybrid metal chalcogenides for high performance supercapacitors. (2023) - Shwetha, K.P.; Athreya, Yash; Suraj, L.; Kumar Rastogi, Chandresh; Sudha Kamath, M.K.; Natarajan, K.; Khosla, Ajit; Manjunatha, C.
Abstract: The pursuit for high-performance supercapacitive materials with high power density identical to conventional capacitors and high energy density comparable to typical batteries has never ceased interest among the research world. As a consequence, innovative energy storage solutions such as supercapacitors (SC) were developed to help with the issue of growing energy requirements in the contemporary world. Among the various electrode materials of SC, hybrid metal chalcogenides have received great interest due to its layered structure, rich redox chemistry, fast ion diffusion kinetics, occurrence of multiple oxidation states and morphological tunability. However, application of these materials in practical application is hindered by their low-rate capability and low cyclic stability. Researchers have developed a number of modification techniques to boost their electrochemical behaviour, such as synthesising composites with diverse carbon materials and conductive polymers, hybrid materials with various metallic ions, with other metal chalcogenides, and heteroatom doping. These techniques of obtaining hybrid metal chalcogenides provide synergistic effect for improved electrochemical performance. The urge for understanding the deeper connection between the nature of change and the altered electrochemical performance that results with hybrid metal chalcogenides still continues. This review focuses on the most current approaches to synthesise hybrid metal chalcogenides and comprehensive summary of modification techniques which has elevated the electrochemical performance. This work also outlines the challenges and prospective future research on hybrid metal chalcogenides.